Association of Patient-Reported Physician Awareness of Complementary Medicine, Medical Care Experience and Care Quality. (October 2021) - Roydhouse, Jessica K.; Wilson, Ira B.; Gutman, Roee; Wallace, Robert B.; Berman, Tara; Keating, Nancy L.
The aim was to examine the association of patient-reported physician awareness of biological CAM use and patient perceptions of care experience and quality with a population-based study of patients with incident lung and colorectal cancer. This was a secondary data analysis using regression models. Outcomes of interest were patient reports of medical care experience and quality ratings. Among 716 patients who reported biological CAM use, 69% reported their physicians were aware of this. Patients who reported physician awareness of biological CAM use had higher adjusted scores for medical care experience ( + 5.4, 95%CI:2.3, 8.6) and care quality ( + 3.6, 95%CI:−0.3,  + 7.5). These associations suggest that physicians should be encouraged to inquire about biological CAM use.